Evaluation of in-Hospital NT-ProBNP Changes in Heart Failure Patients to Identify the Six-Month Clinical Response Following Cardiac Resynchronization Therapy - Gholamreza Davoodi (Acta Medica Iranica, 2014)
N-terminal pro β-type natriuretic peptide (NT-proBNP) is a valuable marker for monitoring the response to treatment in patients with heart failure. Based on the clinically observed improvement of heart failure symptoms early after cardiac resynchronization therapy (CRT), we sought to investigate whether CRT induce any significant reduction in the plasma level of NT-proBNP in three days after implantation and whether it is correlated with patients' response at six months. In this prospective study, 21 consecutive patients with severe heart failure (New York Heart Association class 3.19±0.40) who underwent CRT were enrolled. Being alive, no hospitalization due to decompensated heart failure, and improvement of at least one NYHA functional class at six months were classified as clinical responsiveness. The plasma level of NT-proBNP was measured before, three days, and six months after CRT. Clinical evaluation, echocardiographic study, and six-minute walking test were performed before and six months after the procedure. At six months' follow-up, 16 (76.2%) patients were responders. The plasma level of NT-proBNP at three days after CRT increased almost equally in both responder and non-responder groups of patients (∆NT-proBNP was 40.94±135.74 vs. 54.80±88.98); however, at six months' follow-up, the NT-proBNP changes statistically differed across the two groups of patients (P=0.005). According to our findings, NT-proBNP percent deviation from baseline to three days after CRT appears to be not correlated with the patients' clinical response after six months, which was incongruent to the patients' clinical improvement after CRT.